EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN MEATERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA THROUGH MACRO MEDIA FLASH DI KELAS XI SMA NEGERI 1ANGKOLA SELATAN - Risma Yanti Hutabarat (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2019)
ABSTRACT The aims of this study is know whether there is a significant influence of using MEA learning model through macro media flash on students’ mathematic creative thinking ability at the eleventh grade students of SMA Negeri 1 Angkola Selatan. This research was conducted by applying experimental method (one group pretest post test design) with sample 40 students and they were taken by using simple total sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it was found that: (a) the score of using MEA learning model through macro media flash was 3.2 (very good category), b) the average of students’ mathematic creative thinking ability before using MEA learning model through macro media flash was 44.45 (poor category) and after using MEA learning model through macro media flash was 70.87(good category). Furthermore, by using paired sample ttest and helping SPSS version 17, the result showed the significant value was less than 0.05 (0.000<0.05). It means, there is a significant influence of using MEA learning model through macro media flash on students’ mathematic creative thinking ability at the eleventh grade students of SMA Negeri 1 Angkola Selatan. Keywords: MEA learning model, creative thinking ability